FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA DENGAN MODERASI KEPEMILIKAN MANAJERIAL - Erin Kristi; Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study is conducted to examine the effect of profitability, leverage, firm size, institutional ownership, and independent board of commissioners on earnings management with managerial ownership as the moderating variable. This research is conducted by taking 45 samples of manufacturing companies listed on the Indonesia Stock Exchange consistently during the 2016-2019 period. The samples are selected using purposive sampling method. The data processing technique uses Moderated Regression Analysis which is assisted by the Eviews 10 program. The results in this study indicate that profitability and leverage have a positive effect on earnings management, firm size, institutional ownership, independent board of commissioners, and managerial ownership have no negative effect on earnings management, and managerial ownership has no effect in strengthening the relationship between profitability and firm size on earnings management. The implication of this research is the need to be careful of stakeholders in reading financial reports because of the possibility of earnings management actions that make decisions taken inappropriately.